2019
DOI: 10.22364/bjmc.2019.7.3.08
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Students’ Creativity in Integrating GeoGebra Applets in Solving Geometrical Problems

Abstract: The challenges facing the economy and technologies determine the needs of the labor market for creative professionals, competent specialists, easily adaptive to the technologically changing information environment. Universities are confronted with the main task to experiment and to discover new opportunities for stimulating student creativity, for teaching and learning for mastering specific knowledge, for developing skills and competencies as a key element in their preparation for professional growth. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In a study exploring the training of students in programming through GeoGebra, Velikova and Petkova [68] recruited as their participants 52 future mathematics and informatics teachers who were students at a university. They found that the training was successful when GeoGebra was used as a programming practice.…”
Section: Programming In Geogebramentioning
confidence: 99%
“…In a study exploring the training of students in programming through GeoGebra, Velikova and Petkova [68] recruited as their participants 52 future mathematics and informatics teachers who were students at a university. They found that the training was successful when GeoGebra was used as a programming practice.…”
Section: Programming In Geogebramentioning
confidence: 99%
“…Several efforts to increase creativity found in this review were; the role-play method that also aided in self-discovery learning (Powell et al, 2020), Interdisciplinary Teaching (IDT) can increase divergent creative thinking and team creativity (Liu et al, 2022), interdisciplinary workshops (Ashmore & Moriarty, 2016), project-based educational technology and material development course (Oskay, 2015), The Creative Platform (TCP) (Byrge & Hansen, 2013), GeoGebra Software (Velikova & Petkova, 2019), Mixed Apps software (Andriani & Sagala, 2020), workshops with interactive learning (Siri et al, 2017;Zalloom, 2019), creative responsibility-based teaching (CRBT) (Suyidno et al, 2017), and the Cell Collective (Helikar et al, 2015). The many and varied efforts made by universities to improve teaching for creativity resulted in various outcomes, with findings by Bereczki and Karpati (2018) and Cremin and Chappell (2021), who explained that implementation of creative learning is still scarce in lower education level from early childhood education to senior high school.…”
Section: Efforts By Universities To Foster Student Creativitymentioning
confidence: 99%
“…De la misma manera, genera un gran interés y motivación en las actividades pedagógicas y desarrolla un nivel de comprensión efectivo en el desarrollo de la geometría (Pari Condori et al, 2020). GeoGebra permite crear un entorno creativo para la enseñanza mediante el desarrollo y utilización de Aplicaciones, lo que ha demostrado un aumento de la creatividad de los estudiantes y de las habilidades de resolución de problemas geométricos, además del mejoramiento del rendimiento académico (Velikova & Petkova, 2019).…”
Section: Geogebra Y Su Influencia En El Aprendizaje De Las Matemáticasunclassified